Enhancing Competitiveness of Classification Bodies through OGS Digital Governance and Technological Development Challenges - Wibowo, Aprianto Hani; Sakapurnama, Eko (International Journal of Science and Society, 2024)
This research assesses PT's OGS digital governance system, aiming to address its performance, technology development obstacles, and pursuit of IACS membership recognition. Objectives involve analyzing OGS performance, identifying development challenges, and proposing policy recommendations aligned with the "Road to IACS" policy. Insights from interviews highlight digital strategy alignment with organizational goals, decision-making processes, value delivery, risk and resource management, and performance measurement. PT. BKI (Persero) targets IACS membership by 2024, necessitating internal understanding, commitment, and capability enhancement, alongside external support. Internal support focuses on resource allocation, with 70% to resources and 30% to technology. Digitalization is vital for meeting targets and enhancing service delivery, with strategies spanning various operational aspects and full-circle integration efforts underway. OGS technology development faces challenges such as aligning with IACS standards, identifying assessment findings, and overcoming technical complexities. Strategic plans, resource evaluations, and continuous reviews are vital for overcoming obstacles. Policy recommendations include structured frameworks for assessments, comprehensive barrier assessments, and consistent review mechanisms. Collaboration, training programs, and risk management strategies are advised for effective digital governance and meeting IACS standards.